Estimates of the government of Borno State of Nigeria. 1977; 1996 - Borno State (Nigeria) ([Maiduguri], [publisher not identified], 1976)
This document is a budget estimates presented by the executive Governor of Borno State to the state house of assembly members between 1976-77 financial year. The statement includes anticipatory revenue generation and allocated budget for statutory functions of state government agencies and ministries within the specific year under control.
asm; 11/04/19
Loans
Keywords: Budget; Budget; Expenditures, Public; Borno State (Nigeria); Nigeria